PENGAWASAN PEMERINTAH DAERAH PADA PEREDARAN MINUMAN BERALKOHOL DI KECAMATAN PINOLOSIAN TIMUR KABUPATEN BOLAANG MONGONDOW SELATAN - PAPUTUNGAN, ROSALIA; RURU, JOORIE; TAMPONGANGOY, DEYSI (JURNAL ADMINISTRASI PUBLIK, 2019)
Supervision is a process to ensure that all activities carried out in accordance with what has beenplanned and taking action that can support the achievement of the expected rasults in accordance with thespecified performance. Basically supervision is part of the management function. Supervision has threetypes of supervision: preliminary supervision, councurrent supervision, feedback supervision. Localgovernment is one of the tools in the governance system. This research uses qualitative research typeresearch than is research used to examine natural objects where researchers as a key instrument. Theresults of the study showed that the supervision of the local government in the distribution of alcoholicdrinks in the eastern Pinolosian sub-district of Bolaang Mongondow district, namely the supervision andcontrol of alcoholic drinks, explicitly regulates that only sellers of alcoholic berverages must have a permit.But in the field still found some sellers do not have permission but freely sell these alcoholic drinks for aare no sanctions or confinement measures from the local government. Even thoung regulations on thesupervision and control of alcoholic drinks in south Bolaang Mongondow Regency especially in eastPinolosian subdistrict have been made since 2016, but the presence of policy has not shown changesregarding the distribution of alcoholic drinks in east Pinolosian subdistrict. This is because the function oflocal government supervision of the circulation of alcoholic beverages in the eastern olosian region has notbeen carrien out properly,seeing the reality in the field so far the government has not been consistent inapplying the rules of circulation and alcoholic drinks.if severe alcoholic beverage sellers can still be foundin various places, then the governmrnt will find it increasingly difficult to control the buying interest ofconsumers.although the local government has appealed that especially in east Pinolosian it must be nonalcoholicand pressurize every village head and the shari’ih must make village regulations so thansupervision in east Pinolosian is maximal because the seller or diluent is still free to sell drinks even thoughhe does not have permission from the governmrnt.Keywords: Surveillance, Local government, Alcoholic Drinks